WEB-BASED INTERACTIVE LEARNING MEDIA DEVELOPMENT USING P5.JS ON LIGHT AND OPTICAL DEVICE MODULE FOR HIGH SCHOOL COMPETENCY - Safarina, Sania Salwa; Chrisnanto, Julian Evan; Adiperdana, Budi; Prawiradilaga, Muhammad Galih (Universitas negeri Yogyakarta, 2024)
This research was conducted with the aim of making an interactive learning module for light and optical devices adapted for school students, to improve the performance of education in Indonesia in the Program for International Student Assessment (PISA). By integrating simulation and interactive media using p5.js, students’ understanding and engagement in the subject matter can be improved. The development process includes a comprehensive literature review, interactive object design, simulation creation, and analytical validation of the media by students and learning practitioners. The research also performed analytical calculations and compared the values with the simulated value, then get a fairly small coefficient correlation which is around 0,000427 - 0,021912; 0,003426 - 0.243858; 0,003298 - 0,082615; and 0,001004 - 0,183618 for the convex mirror, concave mirror, convex lens, and concave lens respectively. The effectiveness of the module was evaluated through pretest and posttest, practicality assessment by students, and review by learning practitioners at SMP Muhammadiyah 10 Bandung. The results of this research showed significant improvement in students’ understanding and highlighted the practicality of the module in conveying complex scientific concepts. The research also highlighted the potential of interactive learning media in overcoming educational challenges, especially in science education, and suggests its broader application to improve learning outcomes in a variety of science fields.